Elements of virtual temporal bone surgery: Manipulandum format may be more important to surgeons than haptic device force capabilities. Issue 6 (2nd November 2017) - Unger, Bertram; Sepehri, Nariman; Rampersad, Vivek; Pisa, Justyn; Michael Gousseau,; Hochman, Jordan B.
Abstract : Background: Temporal bone simulations are critiqued for poor drill‐bone interaction. This project appraises the import of increasing haptic device and manipulandum fidelity on the perceived realism of drilling a virtual temporal bone. Virtual surgical contact forces rely on haptic device fidelity and are transmitted through a manipulandum. With identical software, both device hardware and manipulandum may each contribute to realism. We compare the three degrees of freedom (DOF), 3N Geomagic Touch (3D Systems, SC) to a 6DOF, 5.5N HD 2 (Quanser, ON) with the both standard ("HD 2 –Standard") and in‐house customized otic drill manipulandum ("HD 2 –Modified"). Methods: Six otologic surgeons performed three virtual mastoidectomy surgeries on a temporal bone surgical simulator. The HD 2 manipulandum was modified for attached otic drill with gravity compensation and requisite mechanical modifications. Surgeons, in random order, performed the dissection with the different hardware platforms. Results: Two‐tailed t‐tests demonstrate that for the acoustic properties of each simulation, the HD 2 –Modified manipulandum was favored ( p  ≤ 0.0004). For overall similarity of bone, both HD 2 –Standard ( p  ≤ 0.05) HD 2 –Modified ( p  ≤ 0.03)) were favored over the Geomagic; however they were not appreciably different when directly compared to each other. There was no preference for increasing haptic device fidelity in virtual drill bone interaction. In forced rank, users favored the HD 2 –Modified in osseus, vibrational and overall realism, as well as being preferred for education and preoperative rehearsal ( p  ≤ 0.0164). Conclusion: Increasing manipulandum realism was favored. However surprisingly, there was no preference for increased device fidelity, illustrating incremental stiffness had nominal impact. There may be a ceiling to drill bone interaction in virtual haptic simulation. Level of Evidence: 2b.